Effect of different mulch materials on soil properties and on the root growth and yield of maize (Zea mays) and cowpea (Vigna unguiculata) - Maurya, P.R.; Lal, R. (1981)
The effects of different mulch materials on soil temperature and moisture regimes, root and shoot growth, nutrient uptake, and on yield of maize (Zea mays) and cowpea (Vigna unguiculata) was investigated for a tropical Alfisol. The effect of translucent and transparent polythene sheet mulches was compared with that of rice straw mulch, and with unmulched and ridged soil surfaces. The amplitude of diurnal fluctuation in soil temperature at 5 cm depth was 7, 10, 12, 12, and 15°C for straw mulch, bare soil surface, ridged soil, translucent polythene, and transparent polythene mulch, respectively. Root density was generally high under straw mulch and low under unmulched flat and ridged treatments. The maximum shoot elongation rate was 5.5 cm/day with the straw mulch and 3.0 cm/day with the unmulched ridged treatment. In general, translucent polythene and straw mulch materials yield more than unmulched ridges and transparent polythene treatments. Soil temperature, as affected by different mulch and seedbed preparation treatments, had a significant effect on root growth, plant vigour, and grain yield.